Kewenangan Notaris Dalam Pembuatan Akta Peralihan Hak terkait Harta Perkawinan Beda Agama - septiani, indri (Gorontalo Law Review, 2024)
As a public official, the notary has the authority to create authentic deeds concerning joint marital property. It is the notary's responsibility to provide legal education to the parties and the public regarding legal actions related to joint property. Joint marital assets result from a valid marriage, unless there is an agreement regarding the separation of assets. A valid marriage, according to the Marriage Law, is one that is carried out in accordance with the laws of each respective religion and belief. Indonesia is a country with diverse ethnicities and religions, so it is not uncommon to find interfaith marriages. However, interfaith marriages cannot be legally registered according to the law and the country. Until the Supreme Court Circular Letter Number 2 of 2023 was issued, judges were instructed not to grant requests for registration of interfaith marriages.Â Keywords: notary; marital property; interfaith marriages. .